SDSS-III Baryon Oscillation Spectroscopic Survey Data Release 12: galaxy target selection and large-scale structure catalogues - Reid, B.; Ho, S.; Padmanabhan, N.; Percival, W. J.; Tinker, J.; Tojeiro, R.; White, M.; Eisenstein, D. J.; Maraston, C.; Ross, A. J.; Sanchez, A. G.; Schlegel, D.; et al. (My University, 2016)
The Baryon Oscillation Spectroscopic Survey (BOSS), part of the Sloan Digital Sky Survey (SDSS) III project, has provided the largest survey of galaxy redshifts available to date, in terms of both the number of galaxy redshifts measured by a single survey, and the effective cosmological volume covered. Key to analysing the clustering of these data to provide cosmological measurements is understanding the detailed properties of this sample. Potential issues include variations in the target catalogue caused by changes either in the targeting algorithm or properties of the data used, the pattern of spectroscopic observations, the spatial distribution of targets for which redshifts were not obtained, and variations in the target sky density due to observational systematics. We document here the target selection algorithms used to create the galaxy samples that comprise BOSS. We also present the algorithms used to create large-scale structure catalogues for the final Data Release (DR12) samples and the associated random catalogues that quantify the survey mask. The algorithms are an evolution of those used by the BOSS team to construct catalogues from earlier data, and have been designed to accurately quantify the galaxy sample. The code used, designated MKSAMPLE, is released with this paper.
Citation: Reid, B., Ho, S., Padmanabhan, N., Percival, W. J., Tinker, J., Tojeiro, R., . . . Vargas-Magana, M. (2016). SDSS-III Baryon Oscillation Spectroscopic Survey Data Release 12: galaxy target selection and large-scale structure catalogues. Monthly Notices of the Royal Astronomical Society, 455(2), 1553-1573. doi:10.1093/mnras/stv2382
Additional Authors: Thomas, D.;Wake, D.;Beutler, F.;Bizyaev, D.;Bolton, A. S.;Brownstein, J. R.;Chuang, C. H.;Dawson, K.;Harding, P.;Kitaura, F. S.;Leauthaud, A.;Masters, K.;McBride, C. K.;More, S.;Olmstead, M. D.;Oravetz, D.;Nuza, S. E.;Pan, K.;Parejko, J.;Pforr, J.;Prada, F.;Rodriguez-Torres, S.;Salazar-Albornoz, S.;Strauss, M. A.;Schneider, D. P.;Scoccola, C. G.;Simmons, A.;Vargas-Magana, M.
Keywords: Cosmology: Observations; (Cosmology:) Large-Scale Structure Of Universe; Digital Sky Survey; Power-Spectrum Analysis; Luminous Red Galaxies; Low-Redshift Sample